Pilot Study of Cystochon® (Cranberry Extract, Chondroitin Sulfate, and Hyaluronic Acid Complex) in Interstitial Cystitis/Bladder Pain Syndrome - Kwang Taek Kim; Jeong Woo Lee; Hyun-Sop Choe (Urogenital Tract Infection, 2022)
Purpose This study examined whether Cystochon® (cranberry extract, chondroitin sulfate, and hyaluronic acid complex) effectively improves the symptoms and problems of interstitial cystitis/bladder pain syndrome (IC/BPS) patients. Materials and Methods From December 2021 to May 2022, the medical records of IC/BPS patients who visited St. Vincent’s Hospital, Kyung Hee University Medical Center, or Gachon University Gil Medical Center were collected. For the treatment of IC/BPS, the patients were given pentosan polysulfate (PPS) for 12 weeks, with Cystochon® then added and maintained for an additional eight weeks. The OʼLeary–Sant symptom and problem index (Interstitial Cystitis Symptom Index [ICSI], Interstitial Cystitis Problem Index [ICPI]) was used to measure the treatment response. Results After 12 weeks of PPS treatment, ICSI and ICPI improved in all patients. After adding Cystochon® for eight weeks, the ICSI and ICPI indicators improved further. In the ICSI category, significant improvement in symptoms was confirmed in the total ICSI score, particularly in the Q4 (pain-related) questionnaire after adding Cystochon®. In the ICPI category, significant problem improvement was confirmed in the total ICPI score, particularly in the Q1 (frequent urination) and Q4 (pain-related) questionnaires. Although not statistically significant, the remaining indicators generally tended to improve. Conclusions The orally administered combination of cranberry extract, chondroitin sulfate, and hyaluronic acid (Cystochon®) may have a clinically positive effect in patients with IC/BPS. Better clinical improvement can be expected when it is added to the PPS treatment, especially in the category of bladder pain.